Dumbo - Sharpsteen, Ben.; Grant, Joe.; Huemer, Dick, 1898-1979.; Holloway, Sterling; Felton, Verna, 1890-1966.; Brophy, Edward, 1895-1960.; Edwards, Cliff, 1895-1971.; Bing, Herman, 1889-1947.; Baskett, James, 1904-1948.; Bletcher, Billy, 1894-1979.; McLeish, John, 1916-1968.; Wallace, Oliver, 1887-1963.; et al. (Burbank, CA : Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2011)
The stork delivers a baby elephant to Mrs. Jumbo, who happens to be a veteran of the circus, but the newborn is soon ridiculed because of his truly gigantic ears and is dubbed "Dumbo". Dumbo is relegated to the circus' clown acts. It is up to Dumbo's only true friend, Timothy Q. Mouse, to assist Dumbo to achieve his full potential.
"70th anniversary."
Originally produced as a motion picture in 1941.
Based on the book: Dumbo, the flying elephant / by Helen Aberson and Harold Pearl.
Bonus features: Deleted scenes: Deleted sequence: The mouse's tale; Deleted song: "Are you a man or a mouse?" ; Backstage Disney: Taking flight: the making of Dumbo; The magic of Dumbo: a ride of passage; Audio commentary; Sound design excerpt from "The reluctant dragon"; Walt Disney TV introduction; Trailers ; Learn how to take your favorite movies on the go: Disney file digital copy ; Discover Blu-ray 3D with Timon & Pumbaa.
Music, Oliver Wallace, Frank Churchill ; lyrics, Ned Washington ; orchestration, Edward Plumb ; art direction, Herb Ryman [and others] ; animation, Hugh Fraser [and others].
Voices: Sterling Holloway, Verna Felton, Edward Brophy, Cliff Edwards, John McLeish, Herman Bing.
Keywords: Elephants -- Juvenile drama; Circus animals -- Juvenile drama; Circus -- Juvenile drama; Feature films -- Juvenile; Animated films -- Juvenile; Fiction films -- Juvenile; Film adaptations -- Juvenile; Video recordings for the hearing impaired -- Juvenile; Video recordings for the deaf and hearing impaired